KARAKTERISTIK DAN FAKTOR MOTIVASI PENGUNJUNG KE DESA WISATA PERANCAK, JEMBRANA - Ni Putu Ayu Sinta Febriliani; I Made Kusuma Negara; Yohanes Kristianto (Jurnal IPTA)
Perancak Village had abundant and diverse tourism potential that was integrated into one entity as Perancak Tourism Village. The increase in the number of visits each year made this phenomenon interesting to study. The purpose of the study was to understand the characteristics of visitors and analyze the motivational faktors for visiting Perancak Tourism Village. Using quantitative descriptive data analysis techniques, instrument testing, and faktor analysis, with data collection methods including observation, interviews, literature studies, questionnaires, and documentation, and using a sample of 100 respondents obtained through the Slovin formula, the results showed that the majority of visitors were female teenagers, students, or college students, unmarried, using non-commercial accommodation, and organizing their own trips, with a relatively short visit duration. Motivation faktor analysis revealed three main faktors influencing tourist visits to Perancak Tourism Village: Environmental Attraction Faktors (physical attractions and destination atmosphere such as natural environment and climate), External Push Faktors (specific attractions such as romance and special events), and Internal Push Faktors (personal needs for relaxation and escape from routine). Overall, the motivation of visitors to visit Perancak Tourism Village was based on push faktors and pull faktors. Based on the research results, the researcher recommended that managers develop facilities and infrastructure in accordance with the characteristics and motivations of visitors to Perancak Tourism Village.